Optimization of lignin conversion to phenol via partial oxidation of synthesized wastewater containing lignin - Sriprom, Pongsert; Leephisuth, Pornyamon; Assawasaengrat, Pornsawan; Neramittagapong, Arthit; Neramittagapong, Sutasinee (My University, 2020)
This work was to optimize operating parameters for phenol production via partial oxidation. The essential settings, NaOH loading of 4–20 g/L, reaction temperatures of 140–180 °C, and time of 15–45 min, were set as the independent parameters for designing the experiments. A set of tests was generated using Box–Behnken Design (BBD) and performed in a high-pressure reactor at the constant air pressure of 2 bars. A produced phenol concentration was assigned as a response target for evaluating an optimal condition. From the results, a quadratic model of actual data was fit with high accuracy (R2 of 94.1%). A response surface methodology (RSM) was used to evaluate the operating parameters effect on the phenol formation. It showed that the temperature rising affected phenol formation due to the creation of aldehydes at low temperatures and phenol re-polymerization. The presence of NaOH plays an essential role in the production of phenol. It may increase the hydroxyl group's rate to an aromatic ring that yields a high percentage of phenol production. For the reaction time, the longer time gave a higher yield of phenol. However, it slightly increased after 30 min. The predicted optimal condition was determined at the temperature of 161 °C, the NaOH loading of 16.4 mg/L, and the reaction time of 36.2 min. Three experiments were performed at the optimal point to verify the prediction. It was found that the phenol concentration of 30 ± 1 mg/L was yielded at this condition. Moreover, the reaction temperature and the initial pressure of air were not severe. It indicates that the partial oxidation of aqueous lignin solution can produce phenol at mild conditions.
Keywords: Box–Behnken design; Hydrothermal; Lignin; Partial oxidation; Phenol; Response surface methodology